Characterization of the corrosion of iron using a smartphone camera. Issue 2 (3rd March 2016) - Igoe, D.; Parisi, A. V.
ABSTRACT: Smartphone technology provides bountiful opportunities for greater participation in scientific and technological research. Digital camera image sensors have been used for the detection, measurement, and monitoring of corrosion; this work extends that capability to the smartphone. It has been observed that as the corrosion increased in clean iron, red responses decreased proportionally. Green and blue responses quantifiably decreased faster, matching the observed overall reddening as the corrosion increased. Potential noise sources due to the variable texture of the corroded samples had a negligible effect on the results. The effectiveness of this method for the characterization of a smartphone image sensor response to the degree of iron corrosion was reflected in congruent validation tests and errors less than 5%. These results demonstrate that the smartphone may be employed as a low cost and efficient means for the evaluation of surface corrosion.